The process of poverty and the ultra poor - Halder, Shantana R.; Husain, A.M.Muazzam (Research and Evaluation Division, Brac, 2019)
This report focuses on the poverty process - how they become poor, the reasons for their falling into poverty. Poverty is multi-causal. On average 1.7 causes were identified by the respondents. Major causes of poverty were family break-up and land redistribution caused by higher population growth and scarcity of land, poverty inheritence, loss of income earners, coping with incidental crisis and loss of all properties due to natural calamities. The other less important factors of poverty for all but important for specific regions were some bad habit of household heads, river erosion and dowry payment ..